A Quantitative Individual Risk Assessment Method in Process Facilities with Toxic Gas Release Hazards: A Combined Scenario Set and CFD Approach. Issue 1 (2nd October 2018) - Zhang, Bo; Liu, Yue; Qiao, Shen
Abstract : Individuals working in process facilities containing toxic gases may face gas releases and poisoning risks. Many studies regarding individual risk (IR) have been carried out on a worst scenario basis. However, the worst scenario‐based approach cannot represent realistic release risks and may overestimate the IR. In this study, an approach based on complete accident scenario set (CASS) and computational fluid dynamics (CFD) is proposed to quantitatively assess IR of toxic gas release in process facilities. By combining the gas leakage probability and joint distribution probability of the wind direction and speed, a CASS can be built. The CFD method is used to predict the concentration field of gas release and dispersion. Then, the toxic gas concentration can be converted to poisoning fatality probabilities according to the dose–response model. A virtual IR contour can finally be defined by the accumulative assessment of all release scenarios. A case study of an IR area classification in a natural gas process and carbon dioxide recycle terminal processing facility that contains an ammonia refrigeration system is also investigated. With the proposed methodology, the quantitatively classified IR level in process facilities can provide scientific references for safety decision makers. © 2018 American Institute of Chemical Engineers Process Process Saf Prog 38: 52–60, 2019